PP.29.20: SECONDARY HYPERTENSION IN A TUNISIAN INTERNAL MEDICINE DEPARTMENT. (June 2015) - Ariba, Y. Ben; Tliba, A.; Boussetta, N.; Abid, R.; Sayhi, S.; Ajili, F.; Louzir, B.; Labidi, J.; Othmani, S.
Abstract : Objective: Secondary hypertension (SH) refers to arterial hypertension due to an identifiable and often curable cause. It affects approximately 5–10% of the general hypertensive population. SH can be caused by conditions that affect kidneys, arteries, heart or endocrine system. Our aim is to describe the different causes of SH noted in our patients. Design and method: It is a retrospective study of 262 patients followed for a SH at the Internal Medicine Department of the Tunisian Military Hospital from 2000 to 2015. The diagnosis of SH in these patients was suspected in front of clinical and biological arguments and confirmed by the further explorations guiding a suitable therapeutic attitude. Results: Renal causes were the main etiology of SH (254 patients) with acute glomerular nephritis (AGN) in 4 cases, primary chronic glomerular nephropathy (CGN) in 16 cases, including 8 cases of membranous glomerulonephritis, 4 cases of focal segmental glomerulosclerosis and 4 cases of membrano-proliferative glomerulonephritis. Secondary CGN were dominated by diabetic nephropathy in 184 cases, lupus nephropathy in 12 cases and rheumatoid purpura in one case. Congenital kidney diseases were represented by hereditary polycystic kidney disease in 22 patients and Alport syndrome in 2 patients. The renovascular hypertension was noted in 13 cases. The endocrine causes were present in 7 patients (3 cases of Conn syndrome, 2 cases of hyperthyroidism, 1 case of bilateral adrenal hyperplasia and another case of pheochromocytoma). One patient had SH with a cardiac cause that was aortic coarctation. Conclusions: The prevalence of SH exceeds 30 % among patients with resistant hypertension. Common causes include chronic kidney diseases, primary aldosteronism, renovascular hypertension and obstructive sleep apnea. In our study, renal parenchymal disease particularly diabetes is the most common cause of SH. Physicians should be judicious about evaluation of a potentially curable cause of hypertension. Careful clinical evaluation and simple algorithms help avoid unnecessary investigations. In patients with SH, early detection and treatment are important to minimize and prevent irreversible changes in the vasculature and target organs.